2019
DOI: 10.1371/journal.pone.0212742
|View full text |Cite
|
Sign up to set email alerts
|

User violence in mental health services: Adaptation of an instrument. Healthcare-workers’ Aggressive Behavior Scale-Users-Mental Health Version (HABS-U-MH)

Abstract: Background/Objetive According to the World Health Organization, one out of every four violent workplace acts takes place in the health setting. The aims of the study are to adapt the Healthcare-workers’ Aggressive Behavior Scale-Users (HABS-U) to mental health professionals, to establish the frequency of exposure to hostile indicators and to determine which professional group is most exposed. Method Study through qualitative and quantitative m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Specifically, from the organizational perspective of Primary Care, it was observed that delays in care or in the management of appointments generate great discomfort in the user. This has been previously reported in the literature ( 11 , 35 , 38 ). In this line, authors such as Raveel and Schoenmakers ( 13 ) propose increasing the information available to users, this proposal being in line with what was observed in the present study.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Specifically, from the organizational perspective of Primary Care, it was observed that delays in care or in the management of appointments generate great discomfort in the user. This has been previously reported in the literature ( 11 , 35 , 38 ). In this line, authors such as Raveel and Schoenmakers ( 13 ) propose increasing the information available to users, this proposal being in line with what was observed in the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Within Primary Care services, a recent study states that between 54.9 and 78% of the medical personnel are exposed to verbal aggression ( 13 ). These percentages are similar for both nursing and non-health care staff (e.g., clerks), the latter being among the most affected ( 1 , 6 , 8 , 11 , 14 ).…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Emergency departments generally show higher levels of violence [12,13], but, although the mental health area poses a high risk [14], all health professionals have a high rate of violence and harassment. The difference seems to be that those with greater proximity and/or prolonged exposure to the public are at higher risk, namely physicians [15], but particularly nurses [12,16].…”
Section: Introductionmentioning
confidence: 99%